TAFSIR KONTEKSTUAL DAN URGENSINYA BAGI MASYARAKAT ISLAM INDONESIA - Sachidin , Nur (Penerbit CV Tentrem Karya Nusa, 2020)
Interpretation studies in today's society need to involve the accumulation of classical, medieval and modern literature by changing the study methodology which has been dominated by grammatical philological approaches, towards contextualization or actualization of interpretation that leads to the real needs of modern society. Methodological steps for the study of interpretation in society as an alternative in understanding the texts of the Koran towards a contextual approach through the following stages: 1) treating the Koran objectively, 2) understanding the texts of the Qur'an according to the context, 3) understanding word hints (dilalah al-lafzi) by tracing the original linguistic meaning in various forms of usage, both haqiqi and majazi (metaphorical), 4) in understanding the secrets of the expression it is necessary to follow the context of the text, both adhere to the substance of its meaning and their enthusiasm, and 5) the need for contextualization or actualization of the interpretation which leads to the real needs of modern society under the auspices of the objectives of the Qur'an. Key Words: the urgency of interpretation, contextual interpretation, Islamic society